Pay gap and bank performance - XU, JIAHAO (2018)
This paper takes the 2007-2016 listed banks in China as a research sample to study the impact of the internal compensation gap of the senior management team and the salary gap between the senior management team and the ordinary employees on the performance of different types of banks. Through model regression and the introduction of quadratic items, the two pay gaps have a positive impact on bank performance but show a trend of “reverse U”, indicating that this effect has a range effect. Therefore, according to the nature of the bank, we divided the listed commercial banks into joint-stock commercial banks, state-owned commercial banks and city commercial banks for regression analysis. The results show that the internal compensation gap of executives has significant impact on only in joint-stock commercial banks; the compensation gap between executives and ordinary employees has an inverted “U”-type relationship among various banks, indicating that it is very important for banks to maintain a reasonable salary gap. Based on the results, the paper proposes suggestions for incentive mechanisms for different types of banks. Keywords: Pay Gap, Bank Performance, Chinese Banking Sector, Tournament Theory, Behavioral Theory, Psychological Contract Theory.